The Concept of Majeed Amjad “Amoroz” - Dr. Muhammad Naveed; Dr. Tahira Siddiqa (Zaban-o-Adab, 2024)
Majeed Amjad is the prominent Urdu poet of the 20th century. He has significance in poetry subjects, style and technique. Impact of western poets P B Shelly, Keats and Wordsworth can be seen on his poetry. He has discussed philosophical thesis like life, death, time and space. This research article deals with his concept of (Amrooz). An effort has been made to elaborate his concept in the light of his poetry.